A BIBLIOMETRIC STUDY ON THE ASSOCIATIONS BETWEEN LONELINESS AND FAMILY COMMUNICATION - Ibrahim, Nur Nabilah; Othman, Rabihah; Hashim, Anis Aleeya (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study presents a comprehensive bibliometric analysis of scholarly research examining the associations between loneliness and family communication from 2020 to 2025. Drawing on data retrieved from the Scopus database and analyzed using VOSviewer, the study maps the evolution, thematic trends, and geographic distribution of academic output in this field. Findings indicate a sustained growth in publications, with a pronounced focus on the psychological and social dimensions of loneliness, particularly among children and adolescents. The analysis reveals that effective family communication functions as a protective factor against loneliness by fostering emotional support, relational closeness, and a sense of belonging. Conversely, poor family communication is linked to heightened levels of loneliness and associated maladaptive behaviors such as problematic internet use and vulnerability to cyberbullying. The most influential studies emphasize the mental health implications of social isolation, especially in the context of the COVID-19 pandemic. While China, the United States, and the United Kingdom lead in publication volume, citation data suggest high-impact contributions from several European countries. Keyword and co-authorship analyses highlight an emerging focus on youth well-being, caregiver roles, and limited international collaboration. These findings underscore the critical role of familial interactions in addressing loneliness and inform future interdisciplinary research and intervention strategies.